Business Process Reengineering based on Information Economics - syifa annastasia; Sinung Suakanto; Muharman Lubis (Sistemasi: Jurnal Sistem Informasi)
Business Process Reengineering (BPR) is a strategic initiative to achieve fundamental improvements in organizational performance. However, research shows that up to 70% of BPR initiatives fail, often due to unclear value delivery and ineffective process redesign. This study aims to address that gap by redesigning the recruitment and selection process using an information economics approach evaluating the value of information to drive better decision making and resource allocation. The research applied process mapping, identification of non-value-adding activities, and value-based analysis at each stage, followed by the integration of digital tools to streamline workflows and improve data accuracy. A case study in a large organization was conducted to test the effectiveness of the redesigned model. The key findings of this study are its greatest strength and must be explicitly highlighted to convey its impact: the redesigned process resulted in a 67.3% reduction in processing time and a Return on Investment (ROI) of 1,085.17% demonstrating not only operational efficiency but also clear financial gain. These outcomes validate the role of information economics in successful BPR and offer a replicable framework for other organizations. By combining BPR with the discipline of information economics, this study offers a replicable, outcome-oriented framework that addresses one of the most common reasons BPR initiatives fail unclear value delivery. This contribution is particularly critical in HR contexts, where decisions are often qualitative and under digitized. The findings provide actionable guidance for organizations seeking to future-proof their HR processes while avoiding the pitfalls that undermine most BPR efforts.